(untitled) (Bangladesh Journal of Medicine, 2015)
Hyperperfusion syndrome (HPS) is a clinical and neuro radiological entity characterized by headache, vomiting, altered mental status, blurred vision and seizures as well as images suggesting whitegray matter edema involving in most cases posterior regions of the brain, as demonstrated by magnetic resonance image. The development of HPS is most commonly associated with hypertensive encephalopathy, preeclampsia-eclampsia and hemolysis, elevated liver enzymes, low platelets (HELLP) syndrome, and immunosuppressive/cytotoxic drug.While elevated or relatively elevated blood pressure is common in many of these disorders, some hyperperfusion states such as calcineurininhibitor toxicity occur with no apparent pressure rise. In these cases, vasogenic edema is likely due primarily to dysfunction of the capillary endothelium itself, leading to breakdown of the blood-brain barrier. Modern imaging techniques and experimental models suggest that vasogenic edema is usually the primary process leading to neurologic dysfunction; therefore, prompt recognition and management of this condition should allow for clinical recovery if superimposed hemorrhage or infarction has not occurred. Bangladesh J Medicine Jan 2015; 26 (1) : 25-30